The sphinx riddle: the challenges proposed by the national curriculum guidelines for teacher training courses and degrees in History (2002-2019) (Tempo e Argumento, 2021)
The paper subject matter is the curricular guidelines approved by the National Council of Education, since the beginning of this century, prescribing the determinations proposed for teacher training. The three guidelines proposed in this century are confronted with the analysis of 75 curricular paths of training history teachers, through the analysis of egress profiles contained in the pedagogical projects. Throughout the following reflection, we argue that the guidelines promulgated in 2002 and 2015 point to the need for changes, but maintain the training matrix based on the domain of reference knowledge and educational sciences. The guidelines approved in 2019 subvert that matrix, when conceiving teacher training as the appropriation of procedures necessary for the implementation of the proposed curriculum for Basic Education. In the seventeen years that separate 2002 from 2019, History degree courses promoted formal changes that did not address the issues proposed by the guidelines. The article points out, then, the need for History teacher training degrees to pay attention to teacher training, standing up to the issues raised by that council, so as not to succumb to the principle underlying the last approved guidelines: the precariousness of licentiate degrees and teaching.Keywords: teacher training; degrees in History; curriculum; History teaching; legislation.